Investigation of properties of a spatial lattice formed by resonance dielectric spheres - Bryzgalov, G.A. (Вопросы атомной науки и техники, 2004)
The artificial dielectric model is used in creation of a material with the negative ε and µ and in describing electromagnetic wave interactions with vital tissues. The paper presents the theoretical study of the frequency properties and electric field distributions in the spatial cubic lattice at sites of which 216 identical dielectric spheres are placed. Basic oscillation frequencies in the lattice have been defined. Splitting of the frequency performance into bands corresponding to the resonance values of the negative or positive value of εeff is observed. The method for determining the negative values of medium penetrations has been proposed.